The Relation between the ideal of beauty and dependent beauty in Kant's philosophy - Javad Amin; Ali (Journal of Philosophical Investigations, 2015)
Kant organizes his analysis in terms of four moments of the judgment of taste, each of which is supposed to contribute something essential to the complete exposition of the beautiful in "Critique of Judgment". He, in the third moment, based on the key concept analysis of "purposiveness", reaches to the beauty definition "a purposiveness without a purpose" (subjective purposiveness). Below this moment, two concepts of "dependent beauty" and "the ideal of beauty" also arises that aesthetic judgment in both of them is based on an objective purposiveness and a concept indicating nature of the object and the perfection of the object that is considered as default for judgment. This default in dependent beauty is perfection of the object and in the ideal of beauty is a concept from the sum of the rational idea and the aesthetic normal idea, but this point of view is in contradiction with the principle of Kant's aesthetic, which judgment of the beautiful just relies on the subjective purposiveness. This article reviewing the concept of purposiveness and the type of subjective purposiveness in the ideal of beauty and dependent beauty, attempts to explain the aesthetic value of these concepts and their differences and similarities, and finally to determine the position of these two concepts in Kant's philosophy.